MANAJEMEN KEBIJAKAN JARINGAN NIRKABEL MENGGUNAKAN CLOUDPATH ENROLLMENT SYSTEM DENGAN METODE RADIUS - Asep Supriadi; Hendra Supendar; Sulistianto Sutrisno Wanda (Jurnal Teknik Informatika dan Teknologi Informasi, 2022)
ABSTRAK  Many ways are used to make communication easier, One of the most notable changes to computer network communication technology is the use of wireless technology. The technology applied to this computer network is commonly called WLAN (Wireless LAN). WLAN is a local network of wireless areas that uses radio waves as a transmission medium. The conveniences contained in this technology are the triggers for choosing the use of technology in computer networks.  Of all the conveniences offered by wireless, there is a weakness in the application of this technology, namely the security side, which still has many loopholes to be attacked by other parties. Many unauthorized clients can access hotspots, if this happens, it will directly or indirectly harm the ISP (Internet Service Provider). By implementing the Ruckus Cloudpath Application configuration and the use of RADIUS features on the user side. Based on the results of research, the best security system at this time uses the WPA RADIUS (Wireless Protection Autentication Remote Authentication Dial in User Services) method.   Keywords: Wireless, Cloudpath, RADIUS.      Banyak cara yang digunakan untuk membuat komunikasi semakin mudah, Salah satu perubahan paling menonjol pada teknologi komunikasi jaringan komputer adalah penggunaan teknologi wireless. Teknologi yang diterapkan pada jaringan komputer ini biasa disebut WLAN (Wireless LAN). WLAN adalah suatu jaringan lokal area tanpa kabel yang menggunakan gelombang radio sebagai media tranmisinya. Kemudahan-kemudahan yang terdapat pada teknologi ini yang menjadi pemicu pemilihan penggunaan teknologi pada jaringan komputer. Dari semua kemudahan-kemudahan yang ditawarkan wireless ini terdapat suatu kelemahan dalam penerapan teknologi ini yaitu sisi keamanan yang masih banyak terdapat celah untuk diserang oleh pihak-pihak lain. Banyak client yang tidak sah dapat mengakses hotspot,  jika sampai hal ini terjadi maka secara langsung atau tidak langsung akan merugikan pihak ISP (Internet Servis Provider). Dengan menerapkan konfigurasi Aplikasi Ruckus Cloudpath dan penggunaan fitur RADIUS di sisi pengguna. Berdasarkan hasil penelitian sistem keamanan terbaik pada saat ini menggunakan metode WPA RADIUS (Wireless Protection Autentication Remote Authentication Dial in User Services).   Kata Kunci: Wireless, Cloudpath, RADIUS.